New age constraints on magmatism and metamorphism of the Western Sonobari Complex and their implications for an earliest Late Cretaceous orogeny on northwestern Mexico - Alicia Sarmiento-Villagrana; Ricardo Vega-Granillo; Oscar Talavera-Mendoza; Jesús Roberto Vidal-Solano (Revista Mexicana de Ciencias Geológicas)
The Western Sonobari Complex in northwestern Mexico is composed of orogenic metamorphic rocks intruded by a variety of unmetamorphosed plutons and dikes. Petrologic studies and U-Pb geochronology allow dividing the protolith of orthogneisses in the next groups: a) Lower Triassic granodiorite and quartz monzodiorite (249.6–241.3 Ma); b) Upper Triassic granodiorite (213.7–203.5 Ma); c) Upper Jurassic tonalite and granodiorite (162.9–159.1 Ma); and d) Lower Cretaceous diorite (99.9–98.8 Ma). Most of these rocks display amphibolite facies metamorphism, pervasive foliation and several stages of folding. Recrystallized zircon rims yield U-Pb ages of 92.3±4.1 and 90.1±1.3 Ma, which are interpreted to date the orogenic metamorphism. Metamorphic rocks are intruded by numerous post-orogenic granitic dikes dated at 83.9±0.5 to 80.6±1.7 Ma. Geochronology of igneous rocks indicates that the Cordilleran magmatic belts including Triassic and Jurassic plutons continue through northwestern-central Mexico apparently without displacement by the Mojave-Sonora megashear. Correlation based on the age, lithology of protoliths and metamorphic imprint suggests that the earliest Late Cretaceous orogen extends at least from southern California up to Nayarit in west-central Mexico. On the basis of its age and contractional character, the orogenic metamorphism event is related to the collision of the Alisitos arc against the western margin of Pangea but occurring inland the continent not at the contact between these blocks.